Absolutely Self Neat Modules - Hamid, Mohanad Farhan (Iraqi Journal of Science, 2020)
An -module is called absolutely self neat if whenever is a map from a maximal left ideal of , with kernel in the filter is generated by the set of annihilator left ideals of elements in into , then is extendable to a map from into . The concept is analogous to the absolute self purity, while it properly generalizes quasi injectivity and absolute neatness and retains some of their properties. Certain types of rings are characterized using this concept. For example, a ring is left max-hereditary if and only if the homomorphic image of any absolutely neat -module is absolutely self neat, and is semisimple if and only if all -modules are absolutely self neat.